MEMBANGUN KURIKULUM YANG RELEVAN DAN RESPONSIF: PERSPEKTIF DAN PENDEKATAN BARU - Lestari, Williyanti; Hermawan, Asep Herry; Prihantini, Prihantini (Elementar : Jurnal Pendidikan Dasar, 2024)
The curriculum is the core of the education system and is the basis for developing the knowledge, skills and attitudes of students. In this rapidly developing era, the need for a relevant and responsive curriculum is becoming increasingly important. This article involves an in-depth analysis of the literature and a synthesis of various theories and practices related to curriculum development. First, the authors identify some of the key challenges faced in current curriculum development, including rapid social, technological, and economic changes. Second, the authors highlight the importance of understanding the local context in designing relevant curricula. Learner-centred approaches and active learning are also described in this article. Furthermore, the authors introduce new perspectives in building curriculum, namely cross-disciplinary approaches, technology integration, and lifelong learning. The cross-disciplinary approach integrates a variety of subjects and provides a comprehensive understanding of the complex world. Technology integration opens up new opportunities in innovative and collaborative learning. Meanwhile, the lifelong learning approach recognizes the importance of lifelong learning in the face of continuous change. This article also describes some practical implementation examples of these new perspectives and approaches. This includes the use of problem-based projects, experiential learning, and the application of educational technology. Case studies from countries that have adopted this new approach are also presented as evidence of its success. This article concludes that building a relevant and responsive curriculum requires a holistic and future-oriented approach. This involves involving education stakeholders, such as teachers, students, parents, and the community. An effective curriculum must reflect global needs and demands, while taking into account the local context and the characteristics of learners.